2015
DOI: 10.1890/15-1584
|View full text |Cite
|
Sign up to set email alerts
|

Climate-driven habitat size determines the latitudinal diversity gradient in temporary ponds

Abstract: The latitudinal diversity gradient (LDG) has been one of the most documented patterns in ecology, typically showing decreasing species diversity with increasing latitude. Studies of these patterns also used different spatial scales and dispersal traits to better understand the underpinning ecological factors. Seasonal freshwater ecosystems are less studied and may exhibit different patterns because they are more sensitive to climatic variation, which result in an inundation-desiccation cycle. In California, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Brendonck, Jocqué, Tuytens, Timms, and Vanshoenwinkel () found that hydrological stability (defined as frequency and length of hydroperiod) strongly determined FRP invertebrate richness, both locally and regionally. Richness declined along an 800‐km transect, from south to north, in south‐western Australia, corresponding to increased aridity (and thus to hydrological instability, similar to findings in Kneitel () and Timms ()). Brendonck et al () predicted that this trend would reverse, moving further northwards from the arid zone to the tropical Kimberley region, yet high species richness was not observed in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…Brendonck, Jocqué, Tuytens, Timms, and Vanshoenwinkel () found that hydrological stability (defined as frequency and length of hydroperiod) strongly determined FRP invertebrate richness, both locally and regionally. Richness declined along an 800‐km transect, from south to north, in south‐western Australia, corresponding to increased aridity (and thus to hydrological instability, similar to findings in Kneitel () and Timms ()). Brendonck et al () predicted that this trend would reverse, moving further northwards from the arid zone to the tropical Kimberley region, yet high species richness was not observed in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…This also reflected previous patterns in which active dispersers had greater beta diversity than passive dispersers (Soininen et al. , Kneitel ). There are several non‐mutually exclusive explanations for these results.…”
Section: Discussionsupporting
confidence: 87%
“…California vernal pools are seasonal ponds or wetlands whose hydro‐regime is determined by rainfall patterns in this Mediterranean climate (Boix et al. , Kneitel ). The pools typically fill during winter and dry by late spring, but the amount, timing, and distribution of this rainfall are highly variable (Boix et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations